Efficacy and safety of molnupiravir in patients with Omicron variant vaccine breakthrough COVID-19 infection: a randomized, controlled trial - Liu, Yayun; Fan, Shiyong; Xu, Aijing; Ge, Lingling; Wang, Xinyu; Dong, Xu; Xu, Mingxiao; Fan, Wenhan; Zhong, Wu; Liang, Xuesong (Frontiers in Pharmacology, 2023)
Introduction: The randomized, controlled trial of molnupiravir in real-world use during the Omicron wave is scarce . The frequency of hospitalization and death is low, so further research is needed to confirm the virological efficacy of molnupiravir.Methods: A single-center, randomized, controlled clinical trial was conducted, and 111 hospitalized coronavirus disease 2019 (COVID-19) patients were randomly assigned at a ratio of 1:1. Fifty-three patients in the molnupiravir group were administered 800 mg of molnupiravir twice daily for 5 days other than standard therapy, and 58 patients in the control group only received standard therapy in accordance with local guidelines.The antiviral effect and adverse events were evaluated during the follow-up.Results: The median viral clearance time in the molnupiravir group was significantly shorter than that in the control group (P=0.003). Furthermore, patients who started molnupiravir therapy within 3 days had significantly shorter viral clearance time than the controls (P=0.003). In the vaccinated subgroup, molnupiravir therapy was also associated with a shorter viral clearance time (P=0.003). A total of three adverse events, which were minor, were reported in the molnupiravir group. One of them had mild liver function abnormalities, and all of them were resolved without intervention. However, the remission time was similar between the two tested groups.Omicron variant vaccine breakthrough COVID-19 infection patients.